A WS2 / layered silicate nanocomposite catalyst and its preparation and application

By preparing WS2/layered silicate nanocomposite catalyst, the problems of high surface energy and poor uniformity of the polycyclic aromatic hydrocarbon hydrogenation catalyst were solved, and the deep hydrogenation saturation reaction of polycyclic aromatic hydrocarbons was achieved, which significantly improved the catalytic activity and resistance. Sulfurity.

CN116273066BActive Publication Date: 2025-02-11DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111521907.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-13
Publication Date
2025-02-11
Estimated Expiration
2041-12-13

AI Technical Summary

Technical Problem

The existing polycyclic aromatic hydrocarbon hydrogenation catalysts have problems such as high surface energy, poor uniformity, low controllability and large size, resulting in low catalytic activity and making it difficult to achieve deep hydrogenation saturation reaction of polycyclic aromatic hydrocarbons.

Method used

By using nanolayer silicate as a hard template, combining WS2 precursor solution, high-speed shear emulsification and mechanical stirring, etc., to prepare WS2/layer silicate nanocomposite catalysts to form single WS2 nanosheets without agglomeration and single Parallel sandwich composite structure of layered nanolayer silicate disks.

Benefits of technology

The uniform dispersion and high controllability of WS2 nanosheets were achieved, and the hydrogenation saturation reaction activity of polycyclic aromatic hydrocarbons was significantly improved, the selectivity and conversion rate were significantly improved, and the sulfur resistance of the catalyst was also improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003407992060000091
    Figure BDA0003407992060000091
  • Figure HDA0003407992070000011
    Figure HDA0003407992070000011
  • Figure HDA0003407992070000012
    Figure HDA0003407992070000012
Patent Text Reader

Abstract

The present invention relates to the development technology of polycyclic aromatic hydrocarbon hydrogenation saturation catalyst in the field of industrial catalysis technology. 2 / Layered silicate nanocomposite catalyst and its preparation and application. 2 The WS / layered silicate nanocomposite catalyst composition includes 2 Nanosheets and single layered silicate disks, structurally a single agglomerate-free WS 2 WS formed by nanosheets with a size comparable to that of silicate disks 2 ‑Silicate‑WS 2 WS formed by parallel sandwich 2 / layered silicate nanocomposite catalyst. The WS obtained by the present invention 2 / Layered silicate nanocomposite catalysts can be used for the hydrogenation saturation of polycyclic aromatic hydrocarbons such as naphthalene, anthracene and phenanthrene. This technology has achieved WS 2 The parallel sandwich composite of nanosheets and layered silicate monolayer disks, in which WS 2 The length of the two farthest points on the side of the nanosheet is comparable to the diameter of the layered silicate disk, the size of the composite catalyst nanoparticles is uniform, the parallel sandwich composite has a high degree of controllability, the exposure of active sites for catalytic hydrogenation of polycyclic aromatic hydrocarbons is high, and it is universal for the hydrogenation of a variety of aromatic hydrocarbons.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a WS2 / layered silicate nanocomposite catalyst and its preparation and application, belonging to the catalyst preparation technology in the technical field of industrial catalysis. Background Art

[0002] PAHs are hydrocarbons containing two or more aromatic rings. Some PAHs also contain nitrogen, sulfur, oxygen and other heteroatoms and cyclopentane and other structural units. PAHs are highly carcinogenic, mutagenic and teratogenic, and their hydrophobicity and low water solubility make them quickly deposited in the environment. They are recognized as the main pollutants threatening the ecological environment. (Wang W B., et al. JACS, 2003, 125 (35): 10536-7.) The toxicity of PAHs will decrease after hydrogenation and saturation, and they can be widely used as important chemical raw materials and intermediates in the fields of medicine, dyes and fuels.

[0003] The development of efficient hydrogenation catalysts is the core of polycyclic aromatic hydrocarbon hydrogenation technology. Aromatic hydrocarbon hydrogenation catalysts are mainly divided into two categories. One is metal sulfide catalysts, which are mostly used for aromatic hydrocarbon hydrogenation reactions with more impurities. At present, the industry mainly uses CoMo, NiY and NiMo sulfide catalysts supported by γ-Al2O3. In addition to γ-Al2O3, the carrier can also use SiO2, molecular sieves and composite oxides. However, pre-sulfurization treatment is usually required before use, which increases the operating cost, and the hydrogenation activity is not high. The other category is precious metal catalysts. Compared with metal sulfide catalysts, when the raw materials do not contain sulfur compounds, precious metal catalysts can give a very high turnover frequency (TOF) at a lower temperature. For the usual γ-Al2O3-supported precious metal catalysts, a few ppm of sulfur is enough to poison the catalyst, which shows the sensitivity of precious metals to sulfur. Since oil products contain a certain amount of sulfides, they are inevitably affected by sulfur poisoning during the hydrogenation process. In short, the research and development of sulfur-resistant aromatic hydrocarbon hydrogenation catalysts is one of the hot issues that are widely concerned in the field of catalysis today.

[0004] Tungsten disulfide (WS2) is a typical transition metal sulfide, with a sandwich structure SWS sandwich layer as the basic unit. In the sandwich layer, each W atom is covalently bonded to 6 S atoms, forming a triangular pyramid column, belonging to the hexagonal crystal system. The SWS covalent bond within the layer is very strong, and the interlayer is a weak van der Waals force. The thickness of the single layer is about 0.65nm. Low stacking WS2 nanosheets can be prepared by tape stripping or liquid phase intercalation glass (ACS Nano 2013, 7, 791; Science 2011, 331, 568; Nat. Commun. 2015, 6, 8563). However, the prepared WS2 material has high surface energy, poor uniformity and low controllability, and most of the obtained flaky materials are micron-sized, with poor dispersibility, easy to re-agglomerate into large blocks, and poor catalytic hydrogenation performance. CN 201710328302.5 uses a hydrothermal method to hydrothermally prepare a petal-shaped WS2 nanosphere with a size greater than 400nm at 220-250°C. Conventional solvent-thermal or hydrothermally prepared WS2 catalysts usually agglomerate to form self-aggregates of nanosheets in order to reduce surface energy during the crystallization process, and the nanosheets are relatively large in size and have poor catalytic hydrogenation activity. Summary of the invention

[0005] The present invention provides a WS2 / layered silicate nanocomposite catalyst and its preparation and application. The invention realizes the innovation of catalyst structure and the provision of application effect by developing a preparation method, overcomes the shortcomings of the above-mentioned prior art, and the composite with layered silicate disc can effectively solve the problems of low activity of deep hydrogenation saturation reaction of polycyclic aromatic hydrocarbons caused by self-agglomeration, poor particle uniformity, low controllability and large size caused by high surface energy of WS2 nanosheets. The invention realizes the clean and high-value utilization of polycyclic aromatic hydrocarbons, and has universality for rapid hydrogenation saturation of various polycyclic aromatic hydrocarbons.

[0006] The structure of the WS2 / layered silicate nanocomposite catalyst of the present invention is a parallel sandwich composite of a non-agglomerated single WS2 nanosheet and a single-layered nano-layered silicate disk, wherein the thickness of the WS2 nanosheet is 3.0-6.0nm, and the length of the two farthest points on the side is 20-50nm; the diameter of the silicate single-layer disk is 20-50nm, and the thickness is 0.6-2.1nm.

[0007] The present invention provides a method for preparing a WS2 / layered silicate nanocomposite catalyst, which is obtained by the following steps:

[0008] (1) dispersing at least one of natural clay and chemically synthesized layered silicate having a particle size of less than 200 nm in water, and forming a colorless transparent sol under the action of at least one mechanical external force selected from the group consisting of high-speed shear emulsification, mechanical stirring, magnetic stirring, and manual stirring;

[0009] (2) at least one of ammonium tungstate, sodium tungstate, tungsten oxide, phosphotungstic acid and ammonium tetrathiotungstate is used as a tungsten source, at least one of soluble ammonium tetrathiotungstate, sodium sulfide, potassium sulfide, ammonium sulfide, thiourea, carbon disulfide thioacetamide, cysteine ​​and glutathione is used as a sulfur source, and at least one of a reducing sulfur source, hydrazine hydrate, hydroxylamine hydrochloride, oxalic acid and citric acid is used as a reducing agent and dissolved in water, and the pH value of the solution is further adjusted to 3 to 10 by adding 1 to 6 mol / L nitric acid or concentrated ammonia with a mass concentration of 25 to 28%, so as to dissolve the tungsten source and the sulfur source, thereby forming a WS2 precursor solution; the molar ratio of W / S in the precursor solution is 1:2 to 1:4, and the molar ratio of W / reducing agent is 1:1 to 1:6.

[0010] (3) The silicate sol obtained in (1) and the MoS2 precursor solution obtained in (2) are mixed under the action of at least one mechanical external force selected from the group consisting of high-speed shear emulsification, mechanical stirring, magnetic stirring, and manual stirring to form a uniform mixed sol; the mass ratio of silicate to WS2 in the mixed sol is in the range of 0.1 to 10, preferably 0.5 to 2.

[0011] (4) The mixed sol obtained in (3) can be further crystallized at 140-220° C. for 3-72 hours, preferably 180-200° C. for 24-48 hours. The crystallization method can be a common crystallization method such as heating crystallization in a closed system oven, electric furnace, etc., microwave heating crystallization, open system oil bath heating crystallization, etc.; the product separation in the formed gel can be a product separation method such as polar solvent sedimentation separation, vacuum filtration separation and centrifugal separation. The product is washed with deionized water and ethanol. The product can be dried by vacuum drying, freeze drying, CO2 supercritical drying, natural air drying, etc. to obtain a WS2 / layered silicate nanocomposite catalyst.

[0012] The WS2 / layered silicate nanocomposite catalyst prepared by the present invention is used for the liquid phase hydrogenation saturation reaction of polycyclic aromatic hydrocarbons anthracene naphthalene phenanthrene. The liquid phase hydrogenation reaction conditions are: the mass percentage of the catalyst is 0.01% to 1.0% of the raw material, preferably 0.1% to 0.3%; the reaction temperature is 250 to 380°C, preferably 300 to 360°C; the hydrogen reaction pressure is 8 to 14MPa, preferably 10 to 12MPa.

[0013] The characterization analysis of the catalyst of the present invention is as follows: The XRD (X-ray powder diffraction) spectrum of the pure WS2 of the comparative example (see Figure 1 ) can be attributed to WS2 with 2H structure, which has higher crystallinity. Figure 1The XRD spectrum results show that the diffraction peak intensity of the layered silicate in the WS2 / layered silicate nanocomposite catalyst prepared by the present invention is significantly reduced, which means that the crystal phase structure of its lamellae is well maintained, but the order of the stacking structure is weakened. A weaker 2H-WS2 diffraction peak appears in the XRD spectrum of the WS2 / layered silicate nanocomposite catalyst, which indicates that a nano WS2 catalyst is prepared, and the WS2 nanosheets are more uniformly composited with the layered silicate. The TEM (high-resolution transmission electron microscope) characterization results show that the WS2 / layered silicate nanocomposite catalyst is a uniform nano-dispersed sheet, and it can be seen that the nanosheet is a complex of a three-layer parallel sandwich structure of WS2-silicate disc-WS2, without self-agglomeration of WS2 nanosheets, and without the disc stacking of layered silicate. The WS2 nanosheets are uniformly composited with layered silicates in parallel sandwiches. The thickness of a single WS2 nanosheet is 3.0-6.0nm, the number of stacked layers is less than 5-10 layers, and the length of the two farthest points on the side is 20-50nm. (See Figure 2 ). In order to reduce the surface energy, the WS2 nanosheets in the pure WS2 catalyst agglomerate to form irregular and non-uniform self-aggregates with a size greater than 100 nm. The number of stacked layers of the nanosheets is 5 to 10, and the length of the sheet is greater than 40 nm.

[0014] Compared with the prior art, the present invention has the following advantages and effects:

[0015] (1) The present invention uses nano-layered silicate as a hard template. The diameter of the nano-layered silicate material unit sheet is between 20 and 50 nm, which can be dissolved in water to form a charged single-layer sol. The charged single silicate sheet can electrostatically adsorb with ions in the WS2 precursor to reduce the surface energy of WS2, so that WS2 nanosheets grow in parallel on the upper and lower surfaces of the layered silicate monolayer disc, and finally form a WS2-silicate disc-WS2 parallel sandwich composite structure. This process greatly reduces the surface energy of the WS2 nanosheets generated during the crystallization process, avoids their self-agglomeration into large-sized, irregular nanosheet aggregates, and can prepare WS2 / layered silicate nanocomposite catalysts in a one-step process. The diameter size of the layered silicate unit sheet limits the size of the two farthest points on the side of the WS2 nanosheet, so a WS2 / layered silicate nanocomposite catalyst with high controllability and good uniformity can be prepared.

[0016] (2) When the WS2 / layered silicate nanocomposite catalyst prepared by the present invention is used for the hydrogenation saturation reaction of polycyclic aromatic hydrocarbons, its highly exposed catalytic active sites can fully contact with the reaction substrate, thereby achieving rapid hydrogenation saturation of polycyclic aromatic hydrocarbons and deep hydrogenation. The reaction results are shown in Table 1. The selectivity of the octahydrogen product of the polycyclic aromatic hydrocarbon anthracene hydrogenation reaction in the present invention can be as high as 83.1%, and the hydrogenation rate is as high as 56.4%; the selectivity of the octahydrogen product of the phenanthrene hydrogenation reaction is as high as 48.4%, and the conversion rate is as high as 88.1%; the selectivity of the tetrahydrogen product of the naphthalene hydrogenation reaction is as high as 98.8%, and the conversion rate is as high as 71.2%. The polycyclic aromatic hydrocarbon hydrogenation activity of the WS2 / layered silicate nanocomposite catalyst is much higher than that of the pure WS2 catalyst of the control sample. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 XRD patterns of the layered silicate support, pure WS2 obtained in Comparative Example 1, and the WS2 / layered silicate sample obtained in Example 1.

[0018] Figure 2 TEM photos of pure WS2 obtained in Comparative Example 1 and WS2 / layered silicate sample obtained in Example 1. DETAILED DESCRIPTION

[0019] In order to further illustrate the present invention, embodiments are given below, but they do not limit the scope of the present invention.

[0020] Embodiment 1:

[0021] Weigh 1.0g magnesium silicate (magnesium silicate synthesized by hydrothermal method, with an average particle size of 80nm, a single-layer disc size of 35nm, and a thickness of 0.95nm measured by a nano-laser particle size analyzer) and disperse it in 60ml deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 0.1022g ammonium tungstate and 0.2438g cysteine ​​and dissolve them in 60ml water under stirring. Add 5ml of 28% concentrated ammonia water to adjust the pH to 10 to form a red WS2 precursor solution. Under shear emulsification conditions, evenly mix the above magnesium silicate sol and WS2 precursor solution for 10 minutes to obtain a dark red sol. The obtained red sol is transferred to a stainless steel hydrothermal autoclave with a polytetrafluoroethylene lining and crystallized at 200°C in an electric furnace for 24 hours. After cooling to room temperature, filter and separate, wash with deionized water 3 times to obtain a black solid, and freeze-dry for 12 hours to obtain a WS2 / magnesium silicate nanocomposite catalyst.

[0022] The test results of the nano-laser particle size analyzer show that the average particle size of the WS2 / magnesium silicate composite catalyst obtained in this embodiment is 35nm, so WS2 / magnesium silicate is a nano-composite catalyst. HRTEM characterization results show that the WS2 nanosheets are composited on the upper and lower surfaces of a single magnesium silicate disk, thus forming a parallel sandwich composite structure; the thickness of a single WS2 nanosheet is about 4nm, and the length of the farthest two points on the side of the sheet is 35nm.

[0023] The catalyst prepared by the present invention is used for the hydrogenation saturation of polycyclic aromatic hydrocarbons anthracene and phenanthrene in a suspended bed, the mass of anthracene and / or phenanthrene is 3.0g, the tridecane solvent is 30g, the amount of catalyst added is 0.25wt.% of anthracene and / or phenanthrene, the reaction temperature is 350°C, and the reaction is carried out for 4h under the conditions of a hydrogen reaction pressure of 12MPa; the catalyst is used for the hydrogenation saturation of polycyclic aromatic hydrocarbons anthracene and phenanthrene, the amount of catalyst added is 0.25wt.%. The catalyst is used for the hydrogenation saturation of polycyclic aromatic hydrocarbons naphthalene, the amount of naphthalene added is 3.0g, the tridecane solvent is 30g, the amount of catalyst added is 0.25wt.% of naphthalene, the reaction temperature is 300°C, and the reaction is carried out for 6h under the conditions of a hydrogen reaction pressure of 10MPa. The reaction activity results are shown in Table 1. The main deep hydrogenation products are octahydroanthracene and / or octahydrophenanthrene, and tetrahydronaphthalene. The hydrogenation rate or conversion rate of polycyclic aromatic hydrocarbons anthracene, naphthalene and phenanthrene of the catalyst of the present invention is much higher than that of the comparative catalyst.

[0024] Embodiment 2:

[0025] Weigh 1.0g magnesium silicate (magnesium silicate synthesized by hydrothermal method, with an average particle size of 80nm, a single-layer disc size of 35nm, and a thickness of 0.95nm measured by a nano-laser particle size analyzer) and disperse it in 60ml deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 1.0220g ammonium tungstate and 2.4380g cysteine ​​and dissolve them in 60ml water under stirring, add 5ml of 28% ammonia water by mass to adjust the pH to 10 to form a red WS2 precursor solution. Under shear emulsification conditions, evenly mix the above magnesium silicate sol and WS2 precursor solution for 10 minutes to obtain a dark red sol. The obtained red sol is transferred to a polytetrafluoroethylene liner and placed in a microwave synthesizer, and crystallized in an oven at 180°C for 6 hours. After cooling to room temperature, centrifugation is performed, and deionized water is washed 3 times to obtain a black solid. After vacuum drying for 12 hours, a WS2 / magnesium silicate nanocomposite catalyst is obtained.

[0026] The test results of the nano-laser particle size analyzer show that the average particle size of the WS2 / magnesium silicate composite catalyst obtained in this embodiment is 40nm, so WS2 / magnesium silicate is a nano-composite catalyst. HRTEM characterization results show that the WS2 nanosheets are composited on the upper and lower surfaces of a single magnesium silicate disk, thus forming a parallel sandwich composite structure; the thickness of a single WS2 nanosheet is about 4nm, and the length of the farthest two points on the side of the sheet is 30nm.

[0027] The catalyst prepared in this embodiment is used for the suspended bed polycyclic aromatic hydrocarbon anthracene phenanthrene hydrogenation saturation, the mass of anthracene and / or phenanthrene is 3.0g, the tridecane solvent is 30g, the amount of catalyst added is 0.25wt.% of anthracene and / or phenanthrene, the reaction temperature is 380°C, the hydrogen reaction pressure is 8MPa, and the reaction is 4h; for the polycyclic aromatic hydrocarbon anthracene phenanthrene hydrogenation saturation, the amount of catalyst added is 0.25wt.%. The catalyst is used for the polycyclic aromatic hydrocarbon naphthalene hydrogenation saturation, the amount of naphthalene added is 3.0g, the tridecane solvent is 30g, the amount of catalyst added is 0.25wt.% of naphthalene, the reaction temperature is 320°C, and the hydrogen reaction pressure is 8MPa. The reaction is 6h, and the reaction activity results are shown in Table 1. The main deep hydrogenation products are octahydroanthracene and / or octahydrophenanthrene, and tetrahydronaphthalene. The hydrogenation rate or conversion rate of the polycyclic aromatic hydrocarbons anthracene naphthalene phenanthrene of the catalyst of the present invention is much higher than that of the catalyst in Comparative Example 2.

[0028] Embodiment 3:

[0029] Weigh 1.0g Laponite (Bick Additives Co., Ltd., USA, artificially synthesized sodium magnesium silicate lithium salt, average particle size 60nm, single layer disc size 25nm, thickness 0.92nm) and disperse it in 60ml deionized water, and stir mechanically for 1 hour to form a colorless transparent sol. Weigh 2.1761g ammonium tetrathiotungstate and 4ml hydrazine hydrate and dissolve them in 60ml water under stirring, add 5ml mass concentration of 28% ammonia water and adjust the pH to 10 to form a red WS2 precursor solution. Under shear emulsification conditions, the above Laponite sol and WS2 precursor solution are evenly mixed for 10 minutes to obtain a deep red sol. The obtained red sol is transferred to a polytetrafluoroethylene liner and placed in a microwave synthesizer, and crystallized at 180°C for 12 hours. After cooling to room temperature, it is filtered after sedimentation, washed with deionized water 3 times, washed with ethanol 3 times, and a black solid is obtained. After drying naturally for 24 hours, a WS2 / sodium magnesium silicate lithium nanocomposite catalyst is obtained.

[0030] The test results of the nano-laser particle size analyzer show that the average particle size of the WS2 / sodium magnesium silicate lithium composite catalyst obtained in this embodiment is 30nm, so WS2 / sodium magnesium silicate lithium is a nanocomposite catalyst. The HRTEM characterization results show that the WS2 nanosheets are composited on the upper and lower surfaces of a single lithium magnesium silicate disk, thus forming a parallel sandwich composite structure; indicating that the thickness of a single WS2 nanosheet is about 4nm, and the length of the farthest two points on the side of the sheet is 20nm.

[0031] The catalyst prepared in this embodiment is used for the suspended bed polycyclic aromatic hydrocarbon anthracene phenanthrene hydrogenation saturation, the mass of anthracene and / or phenanthrene is 3.0g, the tridecane solvent is 30g, the amount of catalyst added is 0.25wt.% of anthracene and / or phenanthrene, the reaction temperature is 330°C, the hydrogen reaction pressure is 11MPa, and the reaction is 4h; for the polycyclic aromatic hydrocarbon anthracene phenanthrene hydrogenation saturation, the amount of catalyst added is 0.25wt.%. The catalyst is used for the polycyclic aromatic hydrocarbon naphthalene hydrogenation saturation, the amount of naphthalene added is 3.0g, the tridecane solvent is 30g, the amount of catalyst added is 0.25wt.% of naphthalene, the reaction temperature is 280°C, and the hydrogen reaction pressure is 9MPa. The reaction is 6h, and the reaction activity results are shown in Table 1. The main deep hydrogenation products are octahydroanthracene and / or octahydrophenanthrene, and tetrahydronaphthalene. The hydrogenation rate or conversion rate of the polycyclic aromatic hydrocarbons anthracene naphthalene phenanthrene of the catalyst of the present invention is much higher than that of the comparative catalyst.

[0032] Embodiment 4:

[0033] Weigh 0.5g Laponite (Bick Additives Co., Ltd., USA, artificially synthesized sodium magnesium silicate lithium salt, average particle size 60nm, single layer disc size 25nm, thickness 0.92nm) and disperse it in 30ml deionized water, and stir magnetically for 1 hour to form a colorless transparent sol. Weigh 2.1761g ammonium tetrathiotungstate and 4ml hydrazine hydrate and dissolve them in 90ml water under stirring, add 5ml 28% ammonia water by mass to adjust the pH to 10 to form a red WS2 precursor solution. Under magnetic stirring conditions, the above Laponite sol and WS2 precursor solution are uniformly mixed for 1 hour to obtain a dark red sol. The obtained red sol is transferred to a hydrothermal kettle with a polytetrafluoroethylene liner and crystallized in an oven at 200°C for 16 hours. After cooling to room temperature, centrifugation is performed, and deionized water is washed 3 times to obtain a black solid, which is vacuum dried for 24 hours to obtain a WS2 / sodium magnesium silicate lithium nanocomposite catalyst.

[0034] The test results of the nano-laser particle size analyzer show that the average particle size of the WS2 / sodium magnesium silicate lithium composite catalyst obtained in this embodiment is 30nm, so WS2 / sodium magnesium silicate lithium is a nano-composite catalyst. The HRTEM characterization results of the WS2 / sodium magnesium silicate lithium nano-composite catalyst show that the WS2 nanosheets are composited on both the upper and lower surfaces of a single lithium magnesium silicate disk, thus forming a parallel sandwich composite structure; the thickness of a single WS2 nanosheet is about 4nm, and the length of the farthest two points on the side of the sheet is 25nm.

[0035] The catalyst prepared in this embodiment is used for the suspended bed polycyclic aromatic hydrocarbon anthracene phenanthrene hydrogenation saturation, the mass of anthracene and / or phenanthrene is 3.0g, the tridecane solvent is 30g, the amount of catalyst added is 0.25wt.% of anthracene and / or phenanthrene, the reaction temperature is 360°C, and the reaction is carried out for 4h under the conditions of hydrogen reaction pressure of 10MPa; for the polycyclic aromatic hydrocarbon anthracene phenanthrene hydrogenation saturation, the amount of catalyst added is 0.25wt.%. The catalyst is used for the polycyclic aromatic hydrocarbon naphthalene hydrogenation saturation, the amount of naphthalene added is 3.0g, the tridecane solvent is 30g, the amount of catalyst added is 0.25wt.% of naphthalene, the reaction temperature is 290°C, and the reaction is carried out for 6h under the conditions of hydrogen reaction pressure of 10MPa. The reaction activity results are shown in Table 1. The main deep hydrogenation products are octahydroanthracene and / or octahydrophenanthrene, and tetrahydronaphthalene. The hydrogenation rate or conversion rate of the polycyclic aromatic hydrocarbons anthracene naphthalene phenanthrene of the catalyst of the present invention is much higher than that of the comparative catalyst.

[0036] Embodiment 5:

[0037] Weigh 0.1g sodium bentonite (Shanghai Aladdin Biochemical Technology Co., Ltd., natural clay, average particle size 90nm, single-layer disc size 50nm, thickness 1.0nm) and disperse it in 30m deionized water, and stir magnetically for 1 hour to form a colorless and transparent sol. Weigh 1.8364g sodium tungstate, 3.8060g thiourea, and 1.3029g hydroxylamine hydrochloride, dissolve in 90ml water under stirring, add 5ml of 2mol / L dilute nitric acid to adjust the pH to 4 to form a red WS2 precursor solution. Under magnetic stirring conditions, the above-mentioned bentonite sol and WS2 precursor solution are uniformly mixed for 1 hour to obtain a dark red sol. The resulting red sol is transferred to a hydrothermal kettle with a polytetrafluoroethylene liner and crystallized at 200°C in an oven for 16 hours. After cooling to room temperature, direct suction filtration is performed, and deionized water is washed 3 times to obtain a black solid, which is vacuum dried for 24 hours to obtain a WS2 / sodium bentonite nanocomposite catalyst.

[0038] The test results of the nano-laser particle size analyzer show that the average particle size of the WS2 / sodium-based bentonite composite catalyst obtained in this embodiment is 55nm, so WS2 / sodium-based bentonite is a nano-composite catalyst. The HRTEM characterization results of the WS2 / sodium-based bentonite nano-composite catalyst show that the WS2 nanosheets are composited on the upper and lower surfaces of a single sodium-based bentonite disk, thus forming a parallel sandwich composite structure. The thickness of a single WS2 nanosheet is about 6nm, and the length of the farthest two points on the side of the sheet is 45nm.

[0039] The catalyst prepared in this embodiment is used for the suspended bed polycyclic aromatic hydrocarbon anthracene phenanthrene hydrogenation saturation, the mass of anthracene and / or phenanthrene is 3.0g, the tridecane solvent is 30g, the amount of catalyst added is 0.25wt.% of anthracene and / or phenanthrene, the reaction temperature is 300℃, the reaction is carried out for 4h under the conditions of hydrogen reaction pressure of 14MPa; for the polycyclic aromatic hydrocarbon anthracene phenanthrene hydrogenation saturation, the amount of catalyst added is 0.25wt.%. The catalyst is used for the polycyclic aromatic hydrocarbon naphthalene hydrogenation saturation, the amount of naphthalene added is 3.0g, the tridecane solvent is 30g, the amount of catalyst added is 0.25wt.% of naphthalene, the reaction temperature is 250℃, the reaction is carried out for 6h under the conditions of hydrogen reaction pressure of 12MPa, the reaction activity results are shown in Table 1, the main deep hydrogenation products are octahydroanthracene and / or octahydrophenanthrene, and tetrahydronaphthalene, the hydrogenation rate or conversion rate of the polycyclic aromatic hydrocarbons anthracene naphthalene phenanthrene of the catalyst of the present invention is much higher than that of the comparative catalyst.

[0040] Embodiment 6:

[0041] Weigh 0.5g sodium bentonite (Shanghai Aladdin Biochemical Technology Co., Ltd., natural clay, average particle size 90nm, single-layer disc size 50nm, thickness 1.0nm) and disperse in 30m deionized water, 13000r.mp shear emulsification for 10 minutes to form a colorless and transparent sol. Weigh 1.5000g phosphotungstic acid, 3.8060g thioacetamide, 7.2049g citric acid, stir and dissolve in 90ml water, add 5ml of 2mol / L dilute nitric acid to adjust pH to 3 to form a red WS2 precursor solution. Under shear emulsification conditions, the above-mentioned bentonite sol and WS2 precursor solution are uniformly mixed for 10 minutes to obtain a dark red sol. The resulting red sol is transferred to a round-bottom flask with a reflux device and crystallized at 120°C in an oil bath for 60 hours. After cooling to room temperature, it is filtered after sedimentation, washed with deionized water 3 times to obtain a black solid, and freeze-dried for 6 hours to obtain a WS2 / sodium bentonite nanocomposite catalyst.

[0042] The test results of the nano-laser particle size analyzer show that the average particle size of the WS2 / sodium-based bentonite composite catalyst obtained in this embodiment is 60nm, so the WS2 / sodium-based bentonite is a nano-composite catalyst. The HRTEM characterization results of the WS2 / sodium-based bentonite nano-composite catalyst show that the WS2 nanosheets are composited on the upper and lower surfaces of a single sodium-based bentonite disk, thus forming a parallel sandwich composite structure; the thickness of a single WS2 nanosheet is about 4.5nm, and the farthest length of the side of the sheet is 50nm.

[0043] The catalyst prepared in this embodiment is used for the suspended bed polycyclic aromatic hydrocarbon anthracene phenanthrene hydrogenation saturation, the mass of anthracene and / or phenanthrene is 3.0g, the tridecane solvent is 30g, the amount of catalyst added is 0.25wt.% of anthracene and / or phenanthrene, the reaction temperature is 350°C, the hydrogen reaction pressure is 13MPa, and the reaction is 4h; for the polycyclic aromatic hydrocarbon anthracene phenanthrene hydrogenation saturation, the amount of catalyst added is 0.25wt.%. The catalyst is used for the polycyclic aromatic hydrocarbon naphthalene hydrogenation saturation, the amount of naphthalene added is 3.0g, the tridecane solvent is 30g, the amount of catalyst added is 0.25wt.% of naphthalene, the reaction temperature is 300°C, the hydrogen reaction pressure is 11MPa, and the reaction is 6h. The reaction activity results are shown in Table 1. The main deep hydrogenation products are octahydroanthracene and / or octahydrophenanthrene, and tetrahydronaphthalene. The hydrogenation rate or conversion rate of the polycyclic aromatic hydrocarbons anthracene naphthalene phenanthrene of the catalyst of the present invention is much higher than that of the comparative catalyst.

[0044] Comparative Example 1:

[0045] Weigh 0.0552g of ammonium tungstate and 0.1278g of cysteine ​​and dissolve them in 60ml of water under stirring to form a red WS2 precursor solution. The resulting red sol was transferred to a stainless steel hydrothermal autoclave with a polytetrafluoroethylene liner and crystallized at 200°C for 24 hours. After cooling to room temperature, it was separated by suction filtration and washed with deionized water three times to obtain a black solid. After freeze drying for 12 hours, a pure WS2 catalyst was obtained.

[0046] The test results of the nano-laser particle size analyzer show that the average particle size of the pure WS2 catalyst obtained in this comparative example is 210nm. The HRTEM characterization results of the pure WS2 catalyst show that the thickness of the assembled and agglomerated WS2 nanosheets is about 7-10nm, and the farthest length of the side of the sheet is greater than 50nm.

[0047] Comparative Example 2:

[0048] Weigh 1.0g magnesium silicate (magnesium silicate synthesized by hydrothermal method, with an average particle size of 80nm, a single-layer disc size of 35nm, and a thickness of 0.95nm measured by a nano-laser particle size analyzer) and disperse it in 60ml deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 0.1104g ammonium heptamolybdate and 0.2556g cysteine ​​and dissolve them in 60ml water under stirring to form a red MoS2 precursor solution. Mix the above magnesium silicate sol and MoS2 precursor solution evenly for 10 minutes under 13000r.mp shear emulsification conditions to obtain a deep red sol. The obtained red sol is transferred to a stainless steel hydrothermal kettle with a polytetrafluoroethylene lining and crystallized at 160°C in an electric furnace for 24 hours. After cooling to room temperature, filter and separate, wash with deionized water 3 times to obtain a black solid, and freeze-dry for 12 hours to obtain a MoS2 / magnesium silicate composite catalyst.

[0049] The test results of the nano-laser particle size analyzer show that the average particle size of the MoS2 / magnesium silicate composite catalyst obtained in this embodiment is 30nm, so MoS2 / magnesium silicate lithium is a nano-composite catalyst. The SEM characterization results of the MoS2 / magnesium silicate lithium nano-composite catalyst show that the MoS2 component in the catalyst is a single nano-sheet of island-like composite on the surface of a single layered magnesium silicate lithium disk with a size of 20-30nm. The HRTEM characterization results show that the number of layers of a single MoS2 nano-sheet is 1, the thickness of the sheet is about 1.0nm, and the length of the farthest two points on the side of the sheet is 3-5nm.

[0050] Comparative Example 3:

[0051] Weigh 1.0g magnesium silicate (magnesium silicate synthesized by hydrothermal method, with an average particle size of 80nm, a single-layer disc size of 35nm, and a thickness of 0.95nm measured by a nano-laser particle size analyzer) and disperse it in 60ml deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 0.1016g ammonium metavanadate and 0.2632g L-cysteine ​​and dissolve them in 60ml ethylene glycol under stirring to form a VS2 precursor solution. Mix the above magnesium silicate sol and VS2 precursor solution evenly for 10 minutes under shear emulsification conditions to obtain a sol. Transfer the obtained sol to a stainless steel hydrothermal autoclave with a polytetrafluoroethylene liner and crystallize it at 200°C in an electric furnace for 24 hours. After cooling to room temperature, filter and separate it, wash it with deionized water 3 times, and obtain a black solid. After freeze-drying for 12 hours, obtain a VS2 / magnesium silicate nanocomposite catalyst.

[0052] The test results of the nano-laser particle size analyzer show that the average particle size of the VS2 / magnesium silicate composite catalyst obtained in this embodiment is 100nm, so VS2 / magnesium silicate is a nano-composite catalyst. The SEM characterization results of the VS2 / magnesium silicate nano-composite catalyst show that the magnesium silicate disks with a size of 35nm in the catalyst are island-like composites on the surface of the VS2 nanosheets with a size of nearly 100nm. The HRTEM characterization results show that the number of VS2 nanosheets is 6, the thickness of the sheet is about 4nm, and the length of the two farthest points on the side of the sheet is 60nm.

[0053] The catalyst prepared in Comparative Examples 1-3 was used for the suspended bed polycyclic aromatic hydrocarbon anthracene phenanthrene hydrogenation saturation, the mass of anthracene and / or phenanthrene was 3.0g, the tridecane solvent was 30g, the amount of catalyst added was 0.25wt.% of anthracene and / or phenanthrene, the reaction temperature was 350°C, and the hydrogen reaction pressure was 12MPa, and the reaction was carried out for 4h; for the polycyclic aromatic hydrocarbon anthracene phenanthrene hydrogenation saturation, the amount of catalyst added was 0.25wt.%. The catalyst was used for the polycyclic aromatic hydrocarbon naphthalene hydrogenation saturation, the amount of naphthalene added was 3.0g, the tridecane solvent was 30g, the amount of catalyst added was 0.25wt.% of naphthalene, the reaction temperature was 300°C, and the hydrogen reaction pressure was 10MPa, and the reaction was carried out for 6h. The main deep hydrogenation products were octahydroanthracene and / or octahydrophenanthrene, and tetrahydronaphthalene. The hydrogenation rate or conversion rate of the polycyclic aromatic hydrocarbons anthracene naphthalene phenanthrene of the catalyst of the present invention is shown in Table 1.

[0054] Table 1 Polycyclic aromatic hydrocarbon hydrogenation activity of the WS2 / layered silicate nanocomposite catalyst prepared by the present invention and the comparative catalyst.

[0055]

Claims

1. A WS2 / layered silicate nanocomposite catalyst, characterized in that: The nanocomposite catalyst comprises WS2 nanosheets and layered silicate monolayer discs, and structurally, a WS2 / layered silicate nanocomposite catalyst having a WS2-silicate-WS2 sandwich structure is formed by parallel compounding of a single WS2 nanosheet without aggregation and a monolayered silicate nanolayer disc; The mass ratio of layered silicate to WS2 in the WS2 / layered silicate nanocomposite catalyst is 0.1-10, the thickness of a single WS2 nanosheet is 3.0-6.0 nm, and the distance between the two farthest points on the side edge of the surface is 20-50 nm; the diameter of the silicate monolayer disk is 20-50 nm, and the thickness is 0.6-2.1 nm; The preparation method of the nanocomposite catalyst comprises the following steps: (1) Dispersing layered silicate in water to form a colorless and transparent sol under the action of mechanical external force; (2) Use one or a mixture of two or more of ammonium tungstate, sodium tungstate, tungsten oxide, phosphotungstic acid, and ammonium tetrathiotungstate as a tungsten source, dissolve the tungsten source, sulfur source, and reducing agent in water, and adjust the pH value of the solution to 3-10 with 1-6 mol / L nitric acid or concentrated ammonia with a mass concentration of 25-28% to achieve complete dissolution of the tungsten source, thereby forming a WS2 precursor solution; (3) mixing the silicate sol obtained in (1) and the WS2 precursor solution obtained in (2) under the action of an external mechanical force to form a uniform mixed sol; (4) subjecting the mixed sol obtained in (3) to heat treatment and crystallization, cooling the mixed sol, separating the product in the formed gel, and fully drying the mixed sol to obtain a WS2 / layered silicate nanocomposite catalyst; The layered silicate used is one or a mixture of two or more of natural clay and chemically synthesized layered silicate with a particle size of 10 to 200 nm. The sulfur source used is one or a mixture of two or more of soluble ammonium tetrathiotungstate, sodium sulfide, potassium sulfide, ammonium sulfide, thiourea, carbon disulfide, thioacetamide, cysteine, and glutathione; the reducing agent used is one or a mixture of two or more of a reducing sulfur source, hydrazine hydrate, hydroxylamine hydrochloride, oxalic acid, and citric acid, wherein the reducing sulfur source is one or more of cysteine, glutathione, thioacetamide, and thiourea.

2. The WS2 / layered silicate nanocomposite catalyst according to claim 1, characterized in that: The mass ratio of layered silicate to WS2 in the WS2 / layered silicate nanocomposite catalyst is 0.5-2.

3. The WS2 / layered silicate nanocomposite catalyst according to claim 1, characterized in that: The layered silicate used is one or more of magnesium silicate, lithium magnesium silicate, and sodium magnesium lithium silicate.

4. The WS2 / layered silicate nanocomposite catalyst according to claim 1, characterized in that: When a reducing sulfur source is used, it serves as both a sulfur source and a reducing agent; the molar ratio of W / S in the mixed sol is 1:2-1:4, and the molar ratio of W / reducing agent is 1:1-1:

6.

5. The WS2 / layered silicate nanocomposite catalyst according to claim 1, characterized in that: The mass concentration of the layered silicate in the mixed sol in step (3) is in the range of 0.8 to 35 mg / ml; The crystallization temperature of the mixed sol in step (4) is 120 to 220° C., and the crystallization time is 3 to 72 hours.

6. The WS2 / layered silicate nanocomposite catalyst according to claim 1, characterized in that: The crystallization temperature of the mixed sol in step (4) is 140 to 180° C., and the crystallization time is 24 to 48 hours.

7. The WS2 / layered silicate nanocomposite catalyst according to claim 1, characterized in that: The mechanical external force used to form the sol includes one or more of high-speed shear emulsification, mechanical stirring, magnetic stirring, and manual stirring.

8. Use of the WS2 / layered silicate nanocomposite catalyst according to any one of claims 1 to 7 in the liquid phase hydrogenation saturation reaction of one or more of the polycyclic aromatic hydrocarbons naphthalene, anthracene or phenanthrene.

9. The use of the WS2 / layered silicate nanocomposite catalyst according to claim 8, characterized in that: WS2 / layered silicate nanocomposite catalyst can be used for liquid phase deep hydrogenation saturation of liquid phase polycyclic aromatic hydrocarbons, wherein the liquid phase hydrogenation reaction conditions are: the mass percentage of the catalyst is 0.01% to 1.0% of the raw material; the reaction temperature is 250 to 380°C; and the hydrogen reaction pressure is 8 to 14 MPa.

10. The use of the WS2 / layered silicate nanocomposite catalyst according to claim 9, characterized in that: The liquid phase hydrogenation reaction conditions are as follows: the mass percentage of the catalyst is 0.1% to 0.3% of the raw material; the reaction temperature is 300 to 360° C.; and the hydrogen reaction pressure is 10 to 12 MPa.

Citation Information

Patent Citations

  • Petal-shaped tungsten sulfide nano-sphere, preparation method and application of nano-sphere

    CN107188232A

  • Preparation method for hydrogenation catalyst for polycyclic aromatic hydrocarbons, catalyst and application thereof

    CN105772034A

  • Preparation method of high-activity molybdenum disulfide catalyst, catalyst and application thereof

    CN111229259A